Super-homem, versão atualizada afetividade dos homens em seus relacionamentos amorosos e conjugais: uma abordagem junguiana - Conti, Patricia Cristina de (2019)
The major social and cultural transformations that have been taking place point to new proposals for the articulation of masculine and feminine characteristics in the psyche, both individual and collective; they also point to significant changes in the way people deal with their affects. In this scenario, it seems important to broaden the knowledge about the affectivity of men in the contemporary world, as well as to provide subsidies for a good development of the work of professionals who deal with men's mental health. Given these aspects, the present work aimed to understand the subjective experience of the affection of young men in their love and conjugal relationships; and reflect on the ways that they deal with the perception and expression of their affections in these relationships. For that, a study was developed using the qualitative Jungian method. It conducted individual semi-directed interviews, four semi-directed group interviews, and the application of techniques of self-expression (drawing and collage) with 10 men, between the ages of 25-35, who had had a heterosexual relationship for at least two years. The results of this study suggest that the participants value amorous and marital relationships that are lasting and free of normative social parameters, in which there is equal rights, partnership, affinity, intimacy and communication about feelings and emotions. However, they present difficulties in expressing affection and proximity, fearing that they might be misunderstood or even humiliated when they express their feelings and emotions, also because it seems important for them to dedicate themselves to their partners, fulfilling their desires and affirming their value to them. Thus, they often seek to maintain a rational and reserved attitude, while the reflect, elaborate and mature the emotions experienced in conjugality, preferring to express them only when they are clearer and safer to them. It points out that sexuality, an attention to food, moments of pleasure and leisure, persistent encouragement in dialogue, the use of metaphors and music, seem to be great facilitators for reflection, elaboration and communication of affections, as well as of the intimacy and harmony of the couple